Productivity dynamics of Chinese manufacturing firms - Feng, Qu (2020)
China has experienced high-speed catch-up growth with an average annual rate of over 8% in per capita GDP in the past four decades. Using growth accounting, Zhu (Understanding China’s growth: Past, present, and future. Journal of Economics Perspectives, 26(4), 103–124) finds that the growth of total factor productivity (TFP) accounts for 77% of China’s per capita GDP growth during 1978–2007, and argues that China’s TFP growth is mainly driven by resource reallocation due to market liberalization and institutional reforms. This paper aims to estimate China’s aggregate productivity growth by applying three leading methods of estimating firm-level production function on Chinese manufacturing firms during 1998–2007, and quantify the contribution of resource reallocation to productivity growth. In addition, we also empirically compare the three estimation methods in this large data set.